MEMBER'S PERCEPTION OF MARGIN AT BMT ISLAM ABDURAB - Wita Dwika Listihana; Idel Waldelmi; Afvan Aquino (Politeknik Negeri Bengkalis, 2022)
The perception of BMT members on the application of margin data reveals that the level of perception of members shows an average result (3.75) which in this case is in the category of good/agree to the application of the margin that has been applied by BMT Islam Abdurab, meaning that the perception of members on the application of the margin itself by BMT on members must be further increased and the temperature is the same as the margin itself and the data also reveals that the average level of the margin application factor on BMT with a score of (3.88) the data obtained is in the good/agree category, but in terms of This is a factor that influences the application of margin by BMT to members, which must be improved in terms of the three indicators, namely attitude, situational and target. This research was carried out at BMT Islam Abdurab and the population and sample were members of the BMT. This research uses descriptive qualitative method..Keywords: Perception, Margin, BMT